Evaluation of Alfalfa Plants Growth Irrigated with Arsenic Contaminated Water - Aslan, Sukru; Ozturk, Mustafa; Demirbas, Ahmet; Karakoy, Tolga (European Scientific Journal, ESJ, 2018)
The natural and anthropogenic process cause arsenic contamination of waters and creates serious environmental problems throughout the world. Due to the alfalfa is an important crop in diverse farming systems, it has been grown almost 33% of Turkey’s cropland. In this experimental study, effect of As on the alfalfa plant growth and As accumulation in the shoot of the alfalfa was determined. The accumulation of As in shoots as well as growth of alfalfa at various As contaminated water was evaluated. Alfalfa plants were grown in a greenhouse on a soil amended with different concentrations of As (control, 0.51.01.52.02.53.04.06.08.0 mg/L). In this study, data of two harvest samples were presented. Experimental results indicated that the irrigation with Ascontaminated water of alfalfa cause dry weight increase compared to control pots. As accumulation in the shoots of alfalfa plant increase with increasing As concentrations in the irrigation waters. As accumulation in the shoots at the 2 nd harvest samples were higher than the 1 st samples. However, As accumulation differences between the 1 st and 2 nd samples decreased when the As concentrations in the irrigation water was higher than 4 mg/L.